Down Regulation of miR200c Promotes Radiation‐Induced Thymic Lymphoma by Targeting BMI1. Issue 6 (June 2014) - Cui, Jianguo; Cheng, Ying; Zhang, Pei; Sun, Mingjuan; Gao, Fu; Liu, Cong; Cai, Jianming
ABSTRACT The miR‐200c has recently been implicated in the epithelial to mesenchymal transition (EMT) process by directly target the EMT related transcriptional factors ZEB1 and ZEB2. The expression of this miRNA is inversely correlated with tumorgenecity and invasiveness in several human cancers. However, little is known about the expression and targets of the miR‐200c in radiation carcinogenesis. Here in this study, using a split radiation induced thymic lymphoma (RITL) model in BALB/c mice, we found that miR‐200c is down‐regulated in RITL samples. Cell death and apoptosis in lymphoma cells was induced by miR‐200c mimic while decreased by miR‐200c inhibitor. Computational analysis found a putative target site of miR‐200c in the 3′UTR of one of the polycomb group (PcG) protein BMI1 mRNA, which was verified by a luciferase reporter assay. Forced over‐expression of miR‐200c decreased the level of BMI1 protein and moreover, over‐expression of BMI1 rescued the biological effects of miR‐200c, indicating BMI1 is a direct mediator of miR‐200c functions. Furthermore, the BMI1 expression level was up‐regulated and inversely correlated with miR‐200c in RITL samples. Finally, our data also indicates that Adenovirus over‐expression of pre‐miR‐200c reduced tumorgenesis in vivo. Taken together, we conclude that down‐regulated expression of miR‐200c and up‐regulation of its direct target BMI1 in radiation‐induced thymic lymphoma, which may indicate a novel therapeutic method for RITL through induction of miR‐200c or inhibition of BMI1. J. Cell. Biochem. 115: 1033–1042, 2014. © 2013 Wiley Periodicals, Inc.